2016
DOI: 10.1016/j.jad.2015.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Life adversity in depressed and non-depressed older adults: A cross-sectional comparison of the brief LTE-Q questionnaire and life events and difficulties interview as part of the CASPER study

Abstract: 250wBackground: There is a paucity of research on the nature of life adversity in depressed and nondepressed older adults. Early life events work used in-depth interviews; however, larger epidemiological trials investigate life adversity using brief questionnaires. This study investigates the type of life adversity experienced in later life and its association with depression and compares adversity captured using a brief (LTE-Q) and in-depth (LEDS) measure.Methods: 960 participants over 65 years were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
3
19
0
1
Order By: Relevance
“…Individuals who experienced higher cumulative SLEs had higher odds of reporting specific health problems such as frequent back pain, diseases of lungs, joint, and gout; vidual and hearing impairment, fatigue, depression, insomnia, and memory decline by more than two folds. These findings were consistent with the previous studies where strong association was shown between severe stressful events with poor physical functioning, higher risk of disabilities, and poor mental health [6][7][8][9][10][11][12][13][14][15][16][17]. Likewise, as observed in the past study [18,19], a significant positive relationship was also found between cumulative SLEs and psychological distress in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Individuals who experienced higher cumulative SLEs had higher odds of reporting specific health problems such as frequent back pain, diseases of lungs, joint, and gout; vidual and hearing impairment, fatigue, depression, insomnia, and memory decline by more than two folds. These findings were consistent with the previous studies where strong association was shown between severe stressful events with poor physical functioning, higher risk of disabilities, and poor mental health [6][7][8][9][10][11][12][13][14][15][16][17]. Likewise, as observed in the past study [18,19], a significant positive relationship was also found between cumulative SLEs and psychological distress in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of various life events also varies within social groups and from population to population [5]. Exposure to chronic stressful events significantly increases the vulnerability to a wide variety of physical and mental health outcomes [6][7][8]. SLEs involving death, suicide, or illness of a significant people including children, parents, or sibling may increase the risk of depression or anxiety [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the sample as a whole, the average rate of CLEAR LEs was 2.28 (range 0-8), with 42% (136) of the sample having at least one SLE (see Table 2). This is similar to previously reported rates in interviewed [10] and self-report [12] rates. For LTPs, the average was 1.27…”
Section: Demographics and Prevalence Of Life Eventssupporting
confidence: 92%
“…It captures context, and utilises investigator-based ratings of severity according to precedents to reduce subjective bias [7]. The LEDS is better than self-report measures at capturing LEs [12] and its SLEs (those with high negativity after 10-14 days and focused on the self) show superior effect sizes for depression [13]. Those prior to depression onset are given particular attention as provoking agents [14,15].…”
Section: Life Event Interviewsmentioning
confidence: 99%
“…Previous publications have noted the lower validity of checklists of life events and their lower prediction of depression (Bifulco et al ., ; Donoghue, Traviss‐Turner, House, Lewis, & Gilbody, ). More intensive measures allow for exploration of event features, mining each severe event for characteristics which can be damaging to individuals such as loss, threatened loss (danger), and humiliation.…”
Section: Discussionmentioning
confidence: 99%